Analisis Strategi Penanganan Kredit Macet Berdasarkan Konsep Manajemen Risiko Kredit pada KSP Kopdit Tuke Jung - Jedho, Yulita Ermiana; Herdi, Henrikus; Aurelia, Pipiet Niken (Universitas Nusa Nipa Maumere, 2026)
Non perfoming Loans are one of the main risks faced by savings and loan cooperatives and can impacts the financial stability as well as the sustainability of the cooperativ, s operations. this study aims to analyze strategies for handing non-performing loans based on the concepts of credit risk manajement at KSP Kopdit Tuke Jung Deru Dede Branch. This reserch use a qualitative approach with data collection methods through observation, interviews, and documentation. The data analyzed include non-performing loan data for the period 2022-2024 as well as interview results with the cooperative management. The data analys technique is carried out qualitatively and descriptively by linking field finding to findings to the concept of credit risk manajement, which includes risk identification, measurement, and control. The research result indicate that the increase in non-performing loans is influenced by internal factors such as suboptimal credit supervision, as well as exernal factors such as a decline in income and weak manajerial capacity of member businesses. The strategies for handling non-perfoming loans implemented by KSP Kopdit Tuke Jung include rescheduling, reconditioning, and restructuring. The implemention of these strategies is considered quite effective in helping members fulfil their credit obligations and reducing the cooperative, s risk of losses. Although strengthening credit analysis and post-credit supervision is still needed. This study is expected to serve as an evaluation material and reference for credit unions in improving sustainable risk manajement.